2023
DOI: 10.1111/jpc.16326
|View full text |Cite
|
Sign up to set email alerts
|

Unusual local epidemic of paediatric respiratory syncytial virus during a time of global pandemic

Abstract: Background Western Australia (WA) public health measures to eradicate SARS‐CoV‐2 resulted in a secondary reduction in paediatric respiratory syncytial virus (RSV) admissions. Following an absent expected 2020 winter peak, RSV‐positive admissions surged during the summer of 2020. Aim This report examines the number of RSV‐positive admissions and severities across 36 months to better understand this out‐of‐season epidemic. Methods A retrospective observational study was performed assessing the number and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The viruses that cause bronchiolitis have remained relatively unchanged during this period 16,17 . The COVID‐19 pandemic introduced distinct changes in both the prevalence and seasonality of respiratory virus worldwide, including uncharacteristic peaks in bronchiolitis cases during summer months of 2021 18–23 . In the ongoing respiratory season, surges in respiratory syncytial virus, influenza, and SARS‐CoV‐2 infections have led to widespread respiratory illnesses 9 , 24–27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viruses that cause bronchiolitis have remained relatively unchanged during this period 16,17 . The COVID‐19 pandemic introduced distinct changes in both the prevalence and seasonality of respiratory virus worldwide, including uncharacteristic peaks in bronchiolitis cases during summer months of 2021 18–23 . In the ongoing respiratory season, surges in respiratory syncytial virus, influenza, and SARS‐CoV‐2 infections have led to widespread respiratory illnesses 9 , 24–27 .…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 The COVID‐19 pandemic introduced distinct changes in both the prevalence and seasonality of respiratory virus worldwide, including uncharacteristic peaks in bronchiolitis cases during summer months of 2021. 18 , 19 , 20 , 21 , 22 , 23 In the ongoing respiratory season, surges in respiratory syncytial virus, influenza, and SARS‐CoV‐2 infections have led to widespread respiratory illnesses. 9 , 24 , 25 , 26 , 27 Whether these epidemiological changes have altered the prognosis of bronchiolitis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A second retrospective observational study of 294 children between aged 0-16 years hospitalised with RSV in 2018, reported that 22.4% of hospitalisations were infants 0-1 months (31). Furthermore, they noted that in 2019 and 2020 during the SARS-CoV-2 pandemic, the proportion of RSV hospitalisations in infants aged 0-6 months decreased to 16.3% and 5.4% respectively (31).…”
Section: Combined Hospitalisationmentioning
confidence: 99%
“…One study examined proportions of hospitalised RSV requiring respiratory support before and during the SARS-CoV-2 pandemic (31). From a cohort of 294 children aged 0-16 years hospitalised with RSV, they found a statistically signi cant reduction in the proportion requiring respiratory support in 2020, compared to pre-pandemic levels in 2019 (p = 0.004).…”
Section: Respiratory Supportmentioning
confidence: 99%